Effect of prophylactic clipping in colorectal endoscopic resection: A meta-analysis of randomized controlled studies. Issue 6 (October 2017) - Nishizawa, Toshihiro; Suzuki, Hidekazu; Goto, Osamu; Ogata, Haruhiko; Kanai, Takanori; Yahagi, Naohisa
Background and aim: The efficacy of clipping for preventing delayed bleeding after colorectal endoscopic resection is still controversial. To assess the efficacy of prophylactic clipping, we conducted a meta-analysis of randomized controlled trials. Methods: We searched PubMed, the Cochrane library, and the Igaku-chuo-zasshi database for randomized trials eligible for inclusion in our meta-analysis. We identified seven eligible randomized trials from the database search, and compared the effect of clipping versus non-clipping with respect to delayed bleeding and perforation. Data from eligible studies were combined to calculate pooled odds ratios (ORs). Results: Postoperative bleeding was observed in 41 of 1526 cases (2.7%) without clipping and in 32 of 1533 cases (2.1%) with clipping (OR 0.76, 95% CI: 0.39–1.47, p  = 0.414). There was no significant heterogeneity among the trial results (I-Square = 26.7%, p  = 0.22). In the subgroup analysis based on small tumor size (<20 mm) and large tumor size (≥20 mm), there were no significant differences. Compared with non-clipping, the pooled OR of developing perforation with clipping was 1.00 (95% CI: 0.14–7.25), indicating no significant difference between the two groups. Conclusions: Prophylactic clipping did not decrease the occurrence of delayed bleeding after colorectal endoscopic resection. Clipping could be of interest in patients with a high risk of bleeding (anticoagulation) or large lesions, but with the available trials data to prove this are scarce.